READING TECHNIQUES IN TEACHING ENGLISH TO INTERMEDIATE LEVEL STUDENTS - Mannonova Shakhnoza (Galaxy International Interdisciplinary Research Journal, 2022)
The main purpose of teaching a foreign language is the formation and development of foreign language communicative competence, that is, the ability of students to learn new words and phrases and use them in the process of communication, the ability to analyze their actions and words, the development of horizons, the ability to interest the interlocutor or listener, as well as the development of logic for a competent and consistent presentation of thoughts.